Unraveling The Threads of Tradition: The Transformation of Kepayang (Pangium edule Reinw.) Ethnobotanical Knowledge in Sarolangun, Central Sumatra - Hariyadi, Bambang; Lahmuddin, Andi; Alrasyid, M. Harun; Tira, Bisma Sindi; Ihsan, Mahya; Yelianti, Upik; Waskito, Eko (Media Konservasi, 2024)
For centuries, the Sarolangun community in Central Sumatra has depended on kepayang for its essential roles in nutrition, medicine, environmental conservation, and cultural practices. However, modernization now threatens the preservation of indigenous knowledge and traditions related to kepayang. This study investigates the shifts in ethnobotanical knowledge concerning kepayang in six villages across three sub-districts of Sarolangun Regency, Jambi Province, encompassing urban, peri-urban, and rural landscapes representative of the region’s main kepayang production areas. Using a descriptive-analytical approach, data were collected from 68 participants through in-depth interviews and participatory observations utilizing snowball sampling. Findings reveal the plant’s diverse uses and evolving application patterns, with a broader range of uses in rural areas compared to urban ones. Despite these shifts, kepayang retains its culinary significance throughout the community, symbolizing cultural continuity. Additionally, its role in oral traditions continues to impart moral values to younger generations, supporting collective wisdom essential for conservation. This research advocates for a balanced conservation strategy that integrates ecological preservation with cultural heritage and sustainable development, adapting to local knowledge’s evolution while exploring kepayang's potential for economic benefits within the community.